Dampak Pemberian Ekstrak “Simbagh Utak” (Hydnophytum formicarum) Terhadap Penurunan Kadar Asam Urat Darah pada Mencit (Mus musculus) Jantan Hiperurisemia - Gustria Ernis; Dewi Handayani; Agus Sundaryono (University of Bengkulu, 2020)
One of Bengkulu's local culture is the utilization of medicinal plants by the people of Bengkulu, especially South Bengkulu, namely